Characteristics of sexual violence: Study of 127 cases registered in the Court of Appeals of Cotonou - BIGOT, CÉDRIC EGNONWA PARFAIT; ADOVOEKPE, JEAN MARIE; Agbobli, Yawo Apelete; Ekouevi, Didier; BIGOT, KOFFI ANDRÉ (My University, 2018)
ln republic of Benin, rape is a crime for which the law provides harsh penalties. The perpetrators of that form of crime are tried in the courts of appeal by special jurisdictions: the criminai courts. We conducted a case control study on 127 cases of rape investigated and judged by the court of appeal of Cotonou from 2005 to 2015. This research work points out that victims are exclusively women and girls and that 62.2% of them are children under 13 years of age. As regards offenders, ail of them arc male subjects and young adults in 63.8% of cases. They were acquaintances of the victims in 68.5% of the cases; and they ail confessed to the criminal action with which they were charged. The victims were subject to medical examination 7 times out of 10 without police requisition. Those medical consultations confirmed the presence of injuries caused by extra-genital violence in %18.9 ofvictims. Defloration signs were noted in 79.7% of the girls Jess than 13 years old. The populations and health professionais should be sensitized about victims' identification and sociocultural conditions that may facilitate the commission of those crimes; it is an important action to be carried so as to ensure an efficient fight against sexual violence.
Keywords: Sexual assau1t; Rape; Genital injuries; Forensic-medicine; Benin republic.